Perspectives of control and management of research support foundations with the new legal framework for science, technology and innovation - Silva, Nilton Oliveira da; Freire, Fátima de Sousa; Nascimento Junior, Antônio (Contextus - Revista Contemporânea de Economia e Gestão, 2020)
The study investigated the Brazilian Research Support Foundations’ adherence to the new legal framework for innovation regarding control by results. The law aims to simplify processes and maximize the innovation system, especially its control and accountability. We analyzed scientific articles, documents, and foundations websites from 2018 and 2019. The level of adherence was measured by an index generated from a checklist of points. The results showed that on average the foundations have an unsatisfactory level of adherence. New attributes of the law obtained less adherence. These foundations do not yet have a level of adherence to items that can better demonstrate the results, such as statistical indicators.